If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + 10) = 3(8 + -4m) Reorder the terms: 4(10 + m) = 3(8 + -4m) (10 * 4 + m * 4) = 3(8 + -4m) (40 + 4m) = 3(8 + -4m) 40 + 4m = (8 * 3 + -4m * 3) 40 + 4m = (24 + -12m) Solving 40 + 4m = 24 + -12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12m' to each side of the equation. 40 + 4m + 12m = 24 + -12m + 12m Combine like terms: 4m + 12m = 16m 40 + 16m = 24 + -12m + 12m Combine like terms: -12m + 12m = 0 40 + 16m = 24 + 0 40 + 16m = 24 Add '-40' to each side of the equation. 40 + -40 + 16m = 24 + -40 Combine like terms: 40 + -40 = 0 0 + 16m = 24 + -40 16m = 24 + -40 Combine like terms: 24 + -40 = -16 16m = -16 Divide each side by '16'. m = -1 Simplifying m = -1
| 5(6y-4)=2(3y+14) | | p^2+2pr+r^2-16= | | 2(5x-1)=7(3x-5) | | 6(3m+7)=30 | | 3(2w+4)=54 | | 2(7u-3)=50 | | 5(3p+6)=105 | | 2(5y-4)=12 | | t-4/7=5 | | 1000x^3-1y^6= | | x-(x*0.015)=150 | | x-(x*0.15)=150 | | 2x(2x+8)=0 | | 2x(2x+8)=960 | | 4/8=34 | | X-x*0.10=300 | | m=2.5+0.5n | | -65÷39/2 | | -65÷38/2 | | 2g+5s=125 | | 2n-7/4 | | 6x=10n-18/5 | | e^4-9x=1376 | | 12x+60=36x | | -3x+5y=-37 | | -2y+45=5(y-5) | | 4(u+4)=-5u+7 | | 4u+17=7(u+2) | | 5(y-8)+8y=-14 | | 24=4(x+4)-8x | | 5n-10=4n-1 | | -4u+6(u-4)=-32 |